Understanding the reasons for academic stress in Hong Kong via photovoice: implications for education policies and changes. Issue 2 (3rd April 2021) - Tsang, Kwok Kuen; Lian, Yi
ABSTRACT: The aim of this study is to investigate the reasons for academic stress in Hong Kong and provide recommendations to the government on ways to alleviate this problem. Using photovoice, 15 undergraduate students from a private community college in Hong Kong were invited to take and discuss photographs regarding their lived experiences of learning. Thematic analysis is applied to generate themes from the photovoice data. The results suggest several possible reasons for academic stress, including examination demands, school administration and parents. However, the underlying social reason for academic stress may be the internal contradictions of the education system. That is, the education system purports to value all-round and whole-person education but subordinates this worthy goal to examination results. Thus, the results of the study suggest that the government should address this internal contradiction by considering educational, economic and cultural factors when planning educational policies and/or changes.